Adekuasi Hemodialisis antara Pasien Menggunakan Akses Catheter Double Lumen (CDL) dengan Akses Arteriovenous Shunt (AV SHUNT) - Muslimah, Rukhul Hayati; Ramdani, Meida Laely; Suparti, Sri; Santosa, Agus (Journal of Telenursing (JOTING), 2025)
This study aims to determine the difference in hemodialysis adequacy between patients using Catheter Double Lumen (CDL) access with Arteriovenous Shunt (AV Shunt) access in the Hemodialysis Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital. The method used is quantitative, with a bidirectional cohort study design. The study results showed a difference in hemodialysis adequacy between patients using CDL access and patients using AV Shunt access in the Hemodialysis Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital. After the Mann Whitney test was carried out, significant results were obtained, namely p-value = 0.000 <0.05, meaning that there was a difference in adequacy between patients using CDL access with AV Shunt access in the Hemodialysis Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital with the result that better adequacy was in AV Shunt access. Conclusion: Arteriovenous Shunt (AV Shunt) access has a better adequacy rate than Catheter Double Lumen (CDL) access, as evidenced by the comparative value of AV Shunt and CDL adequacy of 86.6% vs. 44.8%. Keywords: AV Shunt, CDL, Dialysis, Kidney Failure, Hemodialysis